Kemampuan Berpikir Kreatif Siswa Ditinjau dari Kepribadian Sensing-Intuitive - Intan Setia Maharani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
This research is a qualitative descriptive study that aims to determine students' creative thinking abilities in terms of sensing and intuitive personality types. The sample was selected using a purposive sampling method with a total sample of 6 students, consisting of 3 students who had sensing personalities, and 3 other students who had intuitive personalities. The data of students' creative thinking abilities obtained were tested for their validity by using technical triangulation through written tests and interviews. The results of this study indicate that students who have sensing personalities have given more than one answer, resolved differently, and provided detailed solutions. While students who have intuitive personalities have given different solutions and detailed solutions but there are still errors in the given solutions.